2020
DOI: 10.1136/bcr-2020-237617
|View full text |Cite
|
Sign up to set email alerts
|

Acute pericarditis as a primary presentation of COVID-19

Abstract: The COVID-19 pandemic is a highly contagious viral illness which conventionally manifests primarily with respiratory symptoms. We report a case whose first manifestation of COVID-19 was pericarditis, in the absence of respiratory symptoms, without any serious complications. Cardiac involvement in various forms is possible in COVID-19. We present a case where pericarditis, in the absence of the classic COVID-19 signs or symptoms, is the only evident manifestation of the disease. This case highlights an atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 14 publications
0
40
0
13
Order By: Relevance
“…Acute pericarditis as the primary manifestation of COVID-19 has first been described by Kumar et al in a 66 year old farmer with cardiovascular risk factors as hypertension, 40 pack-year smoking history and a significant familial premature coronary disease as opposed to our patient who was a healthy bodybuilder with no comorbidities or cardiovascular risk factors [ 4 ]. Chest pain is the main symptom that revealed pericarditis in both our case reports, and should therefore indicate possible cardiac involvement of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Acute pericarditis as the primary manifestation of COVID-19 has first been described by Kumar et al in a 66 year old farmer with cardiovascular risk factors as hypertension, 40 pack-year smoking history and a significant familial premature coronary disease as opposed to our patient who was a healthy bodybuilder with no comorbidities or cardiovascular risk factors [ 4 ]. Chest pain is the main symptom that revealed pericarditis in both our case reports, and should therefore indicate possible cardiac involvement of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, The European Medicines Agency (EMA) indicated that there is no scientific evidence supporting the use of ibuprofen to worsening condition of COVID-19 patients [ 8 ]. We chose however, to treat our patient using only colchicine at 0.5 mg twice a day, as it is not contraindicated for pericarditis in COVID-19 patients as it has been reported [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, limited data have been published on pericarditis and pericardial effusion in COVID-19, [2][3][4][5][6][7][8] and only one case of constrictive pericarditis was reported. 9 Constrictive pericarditis is characterised by inflammation and fibrotic thickening of the parietal and visceral pericardium, causing a restriction in cardiac filling and leading to hypodiastolic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…This leads authors of this case report to hypothesize a similar pathophysiology occuring in the development of pneumothorax in COVID-19 patients. There are also case reports of COVID-19 causing myocarditis and pericarditis [ 8 - 9 ]. These injuries again appear to be caused by dysregulated inflammation.…”
Section: Discussionmentioning
confidence: 99%